PREDICTION OF PHARMACOLOGICAL ACTIVITIES OF BISCARBAMATE MEE-2 AND ITS DERIVATIVES (Journal of Science-Innovative Research in Uzbekistan, 2024)
In this research work, the biological activities of bis-carbamate MEE-2 and its derivatives were studied in the online pass online virtual screening program for the pharmaceutical and medical industries. As a result of screening, many pharmacotherapeutic activities were identified with a high percentage of the presence of various cytochromes as inhibitors, agonists and substrates. The data obtained will help for further research on these compounds and their use in pharmacology